Physiological mechanisms involved in maintaining the corpus luteum during the first two months of pregnancy (2018)
Maintenance of the corpus luteum (CL) during pregnancy is essential for continuing the elevated circulating progesterone (P4) that is required to maintain pregnancy. The mechanisms that protect the CL during early pregnancy when the non-pregnant animal would typically undergo CL regression have been extensively investigated. It is clear uterine prostaglandin F2α (PGF) causes regression of the CL in non-pregnant ruminants and that maintenance of the CL during early pregnancy is dependent upon secretion of interferon-tau (IFNT) from the elongating embryo. A number of specific mechanisms appear to be activated by IFNT. Most studies indicate that there is an inhibition of oxytocin-induced secretion of uterine PGF. There is also evidence for increased resistance to PGF action, perhaps due to secretion of PGE2 and PGE1 or direct endocrine actions of circulating IFNT. These mechanisms occur concurrently and each may help to maintain the CL during the first month of pregnancy. However, during the second month of pregnancy, IFNT is no longer secreted by the embryo. Attachment of the embryo to the uterus and subsequent placentome development have been linked to silencing of expression from the IFNT gene. In addition, there is some evidence that oxytocin responsiveness of the uterus returns during the second month of pregnancy leading to substantial basal secretion of PGF and perhaps PGF pulses. There is also no evidence that the CL during the second month of pregnancy is resistant to the actions of PGF as observed during the first month. Thus, this manuscript attempts to compare the mechanisms that maintain the CL during the first and second months of pregnancy in ruminants and provides a new, speculative, physiological model for maintenance of the CL during month two of pregnancy that is distinct from the previously-described mechanisms that maintain the CL during the first month of pregnancy.